2010
DOI: 10.4137/ehi.s3149
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Quality of Water from Hand-Dug Wells in Ghana

Abstract: This study focused upon the determination of physicochemical and microbial properties, including metals, selected anions and coliform bacteria in drinking water samples from hand-dug wells in the Kumasi metropolis of the Republic of Ghana. The purpose was to assess the quality of water from these sources. Ten different water samples were taken from different parts of Kumasi, the capital of the Ashanti region of Ghana and analyzed for physicochemical parameters including pH, electrical conductivity, total disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 7 publications
2
29
3
Order By: Relevance
“…The decrease in pH from the upstream to the downstream could be attributed to the presence of dissolved carbonates and bicarbonates, which are recognized to affect pH in surface water (Chapman, 1992). pH values obtained in this study are similar to results obtained by and Nwaedozie (1998), which is optimal when considering that values below 6.5 is acidic and could affect the digestive and lymphatic system due to acidosis (Nkansah et al 2010). Temperature values were between 27.03 -28.47°C.…”
Section: Physico-chemical Parameterssupporting
confidence: 76%
“…The decrease in pH from the upstream to the downstream could be attributed to the presence of dissolved carbonates and bicarbonates, which are recognized to affect pH in surface water (Chapman, 1992). pH values obtained in this study are similar to results obtained by and Nwaedozie (1998), which is optimal when considering that values below 6.5 is acidic and could affect the digestive and lymphatic system due to acidosis (Nkansah et al 2010). Temperature values were between 27.03 -28.47°C.…”
Section: Physico-chemical Parameterssupporting
confidence: 76%
“…Although there is no WHO guideline value, phosphate may not be toxic to humans unless they are present in very high levels where digestive problems could occur. Phosphate concentrations in the water samples were generally lower compared to the values of 0.33-9.30 mg/L reported by Nkansah et al (2010) in hand-dug wells in the Kumasi metropolis of Ghana. The low phosphate levels recorded in this study may possibly be due to its adsorption by soils as well as phosphate deficiency in Ghanaian soils hence, applied phosphate might have been used up by cocoa plants as reported by Ewusi et al (2013).…”
Section: Resultsmentioning
confidence: 78%
“…According to Ansa-Asare, Darko, & Asante (2009), the nature of the geology in an area could also account for low pH values. Additionally, Nkansah, Boadi, & Badu (2010), reported that pH values lower than 6.5 are considered acidic for human consumption and can cause health problems such as acidosis and adverse effects on digestive and lymphatic system. Acidity increases the capacity of the water to also attack geological materials and leach toxic trace metals into the water making it potentially unsafe for human consumption (Kortatsi, 2007).…”
Section: Physico-chemical Properties Of Water Samples From the Study mentioning
confidence: 99%